Influence of reflector materials and core coolant on the characteristics of accelerator driven systems. (November 2017) - Panza, F.; Osipenko, M.; Ricco, G.; Ripani, M.; Saracco, P.
Highlights: Accelerator driven system. Physical effects due to material choice. Fast and slow neutron spectra. Power spatial distribution as related to material choice. Study of composite reflector configurations. Study of effects from coolant. Abstract: In this paper we simulated the behavior of a simple ADS model, based on MOX fuel embedded in solid lead, in terms of multiplication coefficient k eff, thermal power and absolute neutron spectra. Our focus on a subcritical, accelerator-driven system is motivated by the need to guarantee enhanced safety based on the distance from criticality and the dependance of the chain reaction on the external neutron source provided by the accelerator. The studies presented here are meant to expand the scientific reach of a previously proposed low-power ADS as the core apparatus of a research and training center in nuclear technologies, such as to increase the flexibility of the system in terms of accessible neutron spectra. In the first part of the paper, we report on the results obtained when modifying the reflector surrounding the fission core, by replacing pure lead with a layered graphite/lead structure. We found that, by appropriately choosing position and thickness of the graphite and lead layers, it is possible to obtain a "hybrid" system where the neutron spectrum in the core still exhibits a fast character, while the spectrum in the graphite layer is considerably softer, becoming thermal in the most peripheral positions. In order to obtain such a modulation of the neutron spectra from the center of the system to the periphery, a careful choice of the materials has to be made in order to avoid large variations of the local power at the core boundary. However, the smoothness of the power distribution is obtained at the expense of lower values of k eff and the total power of the system. In the second part of the paper, we explored the option of adopting light water as coolant, instead of the helium gas assumed in the initial design. We found that this produces an increase in k eff and thermal power, without significantly perturbing the fast character of the system and without introducing spatial power excursions in any place within the core. The characteristics obtained may allow to design a system where fast, mixed and thermal spectra can be used to expand the scope of the ADS as an irradiation facility.